A Verbal-Visual Intersemiotic Translation Model of Advertisement Slogans - Nia Kurniasih; Harry Nuriman; Jejen Jaelani (FISIP Universitas Atma Jaya Yogyakarta, 2019)
This research departs from observations over messages contained in the advertisement slogans of consumer products, especially those using foreign languages. The aim was to find out if shifts have occurred in the translation processes of the slogans from one language to another. Data analysis was performed on the aspect of verbal (interlingual) translation of the slogansfrom English into Indonesian using Jackendoff’s Conceptual Structure. Jakobson’s intersemiotic translation approach was used to analyze the messages of the verbal slogan translated into their visual language. The results show that translation shifts have occurred, both verbally and visually